Antidepressant drug use and regional prescribing patterns in Germany: results from a large population-based study. (7th February 2022) - Dörks, Michael; Hoffmann, Falk; Jobski, Kathrin
Abstract : Objective: To consider antidepressant prescribing on a population level with a focus on regional prescribing patterns in Germany. Basic methods: Based on data from about 70 million individuals covered by all statutory health insurance funds in Germany in 2010, the prevalence of antidepressant use (overall, for drug classes and individual drugs) was calculated stratified by age and sex. Regional analyses were performed on a state and also on a district level. Main results: The study population comprised 68 427 464 (female: 53.0%) persons, of which 5 052 293 (7.4%) were prescribed at least one antidepressant. The most frequently prescribed drug class was tricyclic antidepressants whereas on a substance level citalopram was most commonly used. Antidepressant prescribing was lowest in children and adolescents (0.2%) and most common in persons aged 70 years and older (13.4%). Women more often received antidepressants than men (9.7% vs. 4.8%). Prevalence of antidepressant use varied between 8.7% (Saarland) and 6.3% (Saxony-Anhalt) and was generally highest in the southwestern and lowest in the eastern states. Accordingly, districts with the highest prevalence were located in the southwestern states. Principal conclusions: Antidepressant use in Germany varied considerably by age and sex and also on a state and district level.